Methods for developing an analytical framework to study the inclusion of information and research skills in higher education curricula - Villegas-Muro, Alejandro; Machin-Mastromatteo, Juan D.; Ascencio-Baca, Gerardo; Tarango, Javier (Qualitative and Quantitative Methods in Libraries; Vol 9 No 4 (2020): December Issue 2020, 2021)
This article sets and describes the six stages of an ongoing research that aims at generating an analytical framework to conduct a worldwide study on how bachelor-level higher education curricula can help in teaching and develops information and research skills. We describe the problem statement behind our research proposal, its research questions and the planned research stages.